Additional records of Heteroptera (Hemiptera) from Argentina - Olivo, Veronica Ines (2009)
New Heteroptera findings of Anthocoridae (1 sp.), Coreidae (5 sp.), Cydnidae (1 sp.), Miridae (6 sp.), Nabidae (2 sp.), and Reduviidae (8 sp.) are given from Argentina. New country records are mentioned for the families Coreidae: Lybius dichrous Stål, Vilga (Vilgula) serrulata Montandon, Vilga (Laevivilga) divaricata Distant; and Reduviidae: Apiomerus flavipennis Herrich-Schaeffer, Rasahus paraguayensis Coscarón, Ricolla femoralis Distant, and R. quadrispinosa (Linné).